On the effect of demand randomness on inventory, pricing and profit - Chua, Geoffrey Bryan Ang (2015)
We consider a stocking-factor-elasticity approach for pricing newsvendor facing multiplicative demand uncertainty with lost sales. For a class of iso-elastic demand curves, we prove that optimal order quantity decreases in demand uncertainty for zero salvage value. This contrasts with fixed-price newsvendor results which depend on the critical ratio. Numerical tests show that optimal order quantity increases in demand uncertainty for high salvage value, low marginal cost, and low price-elasticity. We also report results on optimal price, service level, and profit.